PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR PESERTA DIDIK DI MAN 1 KOTA MAKASSAR - Mastori, Akhmad; Bunyamin, Andi; Mustamin; Syahid, Akhmad; Wahab, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the application of the Mind Mapping learning model, determine student learning outcomes, and analyze the effect of the Mind Mapping learning model on student learning outcomes in the subject of Islamic Cultural History (SKI) for class XI at MAN 1 Makassar City. This study uses a quantitative approach with an ex post facto research type. The study population was 408 students, while the research sample was 80 students determined using the proportionate stratified random sampling technique. Data collection techniques were carried out through questionnaires and documentation. Data were analyzed using descriptive statistical analysis and inferential statistics which include normality tests, linearity tests, multiple linear regression tests, t tests, F tests, and coefficients of determination with the help of the SPSS program. The results of the study indicate that the application of the Mind Mapping learning model consisting of individual Mind Mapping indicators, Collaborative Mind Mapping, and visual and symbol Mind Mapping is in the moderate category. Student learning outcomes in the subject of Islamic Cultural History are also in the moderate category. The results of the inferential analysis indicate that the Mind Mapping learning model has a positive and significant effect on student learning outcomes. This is proven through the results of the F test which obtained an F count value of 35.332 greater than the F table of 2.72 with a significance value of 0.000 <0.05. The results of the t test also show that each Mind Mapping indicator has a significant effect on student learning outcomes. In addition, the coefficient of determination (R Square) value of 0.582 indicates that the Mind Mapping learning model contributes 58.2% to student learning outcomes, while 41.8% is influenced by other factors outside the study. Thus, the Mind Mapping learning model is proven to be effective in improving student learning outcomes in the subject of Islamic Cultural History for class XI at MAN 1 Makassar City.